Individual-level factors associated with the risk of acquiring human Plasmodium knowlesi malaria in Malaysia: a case-control study. Issue 3 (June 2017) - Grigg, Matthew J; Cox, Jonathan; William, Timothy; Jelip, Jenarun; Fornace, Kimberly M; Brock, Patrick M; von Seidlein, Lorenz; Barber, Bridget E; Anstey, Nicholas M; Yeo, Tsin W; Drakeley, Christopher J
Summary: Background: The emergence of human malaria due to the monkey parasite Plasmodium knowlesi threatens elimination efforts in southeast Asia. Changes in land use are thought to be driving the rise in reported P knowlesi cases, but the role of individual-level factors is unclear. To address this knowledge gap we assessed human and environmental factors associated with zoonotic knowlesi malaria risk. Methods: We did this population-based case-control study over a 2 year period in the state of Sabah in Malaysia. We enrolled cases with microscopy-positive, PCR-confirmed malaria who presented to two primary referral hospitals serving the adjacent districts of Kudat and Kota Marudu. We randomly selected three malaria-negative community controls per case, who were matched by village within 2 weeks of case detection. We obtained questionnaire data on demographics, behaviour, and residential malaria risk factors, and we also assessed glucose-6-phosphate dehydrogenase (G6PD) enzyme activity. We used conditional logistic regression models to evaluate exposure risk between P knowlesi cases and controls, and between P knowlesi and human-only Plasmodium spp malaria cases. Findings: From Dec 5, 2012, to Jan 30, 2015, we screened 414 patients and subsequently enrolled 229 cases with P knowlesi malaria mono-infection and 91 cases with other Plasmodium spp infection. We enrolled 953 matched controls, including 683 matched to P knowlesi cases and 270 matched to non- P knowlesi cases. Age 15 years or older (adjusted odds ratio [aOR] 4·16, 95% CI 2·09–8·29, p<0·0001), male gender (4·20, 2·54–6·97, p<0·0001), plantation work (3·50, CI, 1·34–9·15, p=0·011), sleeping outside (3·61, 1·48–8·85, p=0·0049), travel (2·48, 1·45–4·23, p=0·0010), being aware of the presence of monkeys in the past 4 weeks (3·35, 1·91–5·88, p<0·0001), and having open eaves or gaps in walls (2·18, 1·33–3·59, p=0·0021) were independently associated with increased risk of symptomatic P knowlesi infection. Farming occupation (aOR 1·89, 95% CI 1·07–3·35, p=0·028), clearing vegetation (1·89, 1·11–3·22, p=0·020), and having long grass around the house (2·08, 1·25–3·46, p=0·0048) increased risk for P knowlesi infection but not other Plasmodium spp infection. G6PD deficiency seemed to be protective against P knowlesi (aOR 0·20, 95% CI 0·04–0·96, p=0·045), as did residual insecticide spraying of household walls (0·52, 0·31–0·87, p=0·014), with the presence of young sparse forest (0·35, 0·20–0·63, p=00040) and rice paddy around the house (0·16, 0·03–0·78, 0·023) also associated with decreased risk. Interpretation: Adult men working in agricultural areas were at highest risk of knowlesi malaria, although peri-domestic transmission also occurrs. Human behavioural factors associated with P knowlesi transmission could be targeted in future public health interventions. Funding: United Kingdom Medical Research Council, Natural Environment Research Council, Economic and Social Research Council, and Biotechnology and Biosciences Research Council.